Learning-oriented evaluation: A tool for promoting institutional learning and program improvement - Watts, J. (2005)
Evaluation processes of all types, including monitoring, review and impact assessment, offer unique opportunities for learning and provide useful feedback on what works and what doesn’t, and the reasons for success or failure. Involving staff members, partners and beneficiaries in the evaluation process allows them to reflect on their work, revisit their understanding of the project’s goals and activities, assess their effectiveness and take ownership of the evaluation findings. The knowledge created and the lessons learned through evaluation subsequently provide a basis for better project planning and implementation. This Brief outlines an evaluation approach that promotes learning and program improvement; it contrasts this approach with accountability-focused evaluation and it provides an example of learning-oriented evaluation from within the Consultative Group on International Agricultural Research (CGIAR).